2023
DOI: 10.1039/d3ew00211j
|View full text |Cite
|
Sign up to set email alerts
|

Advancements in biofilm carriers and gas-permeable membranes: assessment of zeolite technologies for shortcut nitrogen removal applications in wastewater

Abstract: The partial nitrification-anammox (PNA) process and other shortcut nitrogen removal processes have been widely studied because of their potential to offer cost savings during wastewater treatment; nevertheless, sustainable examples of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 41 publications
(118 reference statements)
0
12
0
Order By: Relevance
“…This differs from what one might expect based on previous research that showed that zeolite was still capable of exchanging ammonium when covered by biofilm. 40 Nevertheless, those previous results were obtained under equilibrium conditions and not under conditions that were dominated by sorption kinetics. 40 As with the Z and C carrier-containing reactors, no nitrite was detected in the influent or the effluent.…”
Section: Resultsmentioning
confidence: 82%
See 4 more Smart Citations
“…This differs from what one might expect based on previous research that showed that zeolite was still capable of exchanging ammonium when covered by biofilm. 40 Nevertheless, those previous results were obtained under equilibrium conditions and not under conditions that were dominated by sorption kinetics. 40 As with the Z and C carrier-containing reactors, no nitrite was detected in the influent or the effluent.…”
Section: Resultsmentioning
confidence: 82%
“…40 Nevertheless, those previous results were obtained under equilibrium conditions and not under conditions that were dominated by sorption kinetics. 40 As with the Z and C carrier-containing reactors, no nitrite was detected in the influent or the effluent. Nitrate was detected in the influent to the reactors at 0.47 ± 0.40 mg N L −1 , and subsequently decreased in the effluent of both the ZP and CP carrier reactors (Fig.…”
Section: Resultsmentioning
confidence: 82%
See 3 more Smart Citations